2017
DOI: 10.4187/respcare.05268
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Hypoxemia and Other Factors That Influence the Response to Aerosolized Prostacyclin in ARDS

Abstract: Aerosolized prostaglandin I improves oxygenation in approximately 60% of ARDS cases. A favorable response was most strongly associated with baseline P /F and C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 52 publications
4
26
3
1
Order By: Relevance
“…The other explanation might come from subjects’ baseline oxygenation. Kallet et al found that the baseline oxygenation was significantly related to ARDS patients’ response to iEPO while patients with lower baseline oxygenation had less response to iEPO [27]. In our study, all the subjects’ baseline SpO 2 /F I O 2 was ≤150, which was in the lowest group in Kallet et al’s study.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…The other explanation might come from subjects’ baseline oxygenation. Kallet et al found that the baseline oxygenation was significantly related to ARDS patients’ response to iEPO while patients with lower baseline oxygenation had less response to iEPO [27]. In our study, all the subjects’ baseline SpO 2 /F I O 2 was ≤150, which was in the lowest group in Kallet et al’s study.…”
Section: Discussionsupporting
confidence: 39%
“…In Kallet et al’s study on mechanical ventilation, 208 ARDS subjects were included, and only 62% responded to iEPO. The response rate decreased if the primary source of ARDS was lung related [27]. This finding might explain the low response rate (45%) in our study as all of the subjects had pulmonary etiology.…”
Section: Discussionmentioning
confidence: 71%
“…Jedoch wurde auch hier keine Zunahme der Überlebensrate beobachtet. Vielmehr wird ebenfalls der pulmonal-vaskuläre Widerstand gesenkt, jedoch besteht gleichzeitig die Gefahr einer systemischen Kreislaufinstabilität durch arterielle Hypotension [69].…”
Section: Statineunclassified
“…2,[5][6][7][8] Alternative strategies such as conservative fluid management, corticosteroids, and extracorporeal membrane oxygenation (ECMO) have resulted in improved oxygenation and lung compliance only. 2,[9][10][11] Inhaled epoprostenol and nitric oxide have been evaluated in refractory hypoxemia with comparable outcomes; significant cost savings have been associated with epoprostenol. 12,13 To reduce practice variation and improve outcomes, an inhaled epoprostenol utilization policy was implemented.…”
mentioning
confidence: 99%